Urgensi Media E-Comic dalam Pembelajaran Sosiologi di SMA - Nada'a Asyifa Maharani; Reno Fernandes (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The development of information technology in the 21st century has resulted in various changes in society, one of which has occurred in the education sector. The 21st century is also called the era of the industrial revolution 4.0, where life is getting faster and more open. In order to adapt to this century, humans need life skills called 21st-century skills. To acquire 21st-century skills, learning must be adaptive to developments because information technology is fundamental and must be mastered and applied in the learning process. This study aims to determine the need for e-comic learning media in sociology subjects. This study uses quantitative research methods with research subjects of class XI IPS students with a sample of 35 people and two sociology teachers. The instrument used in this research is a questionnaire. The observational data analysis technique was used in the form of quantitative data, which was obtained from a questionnaire analysis of the needs of E-comic learning media for students and teachers. The analysis of the data was carried out descriptively. Based on the questionnaire, it is known that the teacher has never used e-comic learning media. The results showed that the need for e-comic media for students was 99.36%, and for teachers, it was 100%. In conclusion, students' needs for e-comic learning media in sociology subjects must be considered and fulfilled so that the learning process can run optimally.